The library: a diverse setting for the promotion of reading - Chaves Salgado, Lorena (2018)
The public library and the school library are projected and understood from the spaces mediated by activities and experiences linked to the concept of "promotion of reading". Both libraries constitute a fundamental means of integral formation for life through reading as a social and cultural practice; by their nature of democratic institutions open to the whole of society, they have to respond to the needs of individuals and groups.